Analisis Strategi Manajemen Kelembagan di PKBM Al-Ikhram - Sani Susanti; Anugrah Setiawan; Geovani A K br Sitepu; Ela Saputri; Fitri Salsabila; Nadya Jollin Wahyudi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to analyze the institutional management strategies implemented at the Al-Ikhram Community Learning Activity Center (PKBM). Using a qualitative approach, this research analyzes the management strategy at PKBM Al-Ikhram as a non-formal educational institution that focuses on community empowerment through the learning programs it provides. Data was collected through in-depth interviews with managers, direct observation regarding the management strategies that have been implemented. The results of the analysis show that PKBM Al-Ikhram has succeeded in implementing various institutional management strategies that support the effectiveness and sustainability of the institution. These strategies include human resource management, development of relevant curricula, use of information technology, as well as cross-sector collaboration efforts. In addition, challenges faced in implementing management strategies were also identified, such as limited resources and changes in educational policies.